Providing social support to female Olympic athletes - Poucher, Z. A.; Tamminen, K. A.; Kerr, G. (Journal of Sport & Exercise Psychology, 2018)
Support providers may experience positive and negative outcomes associated with supporting others. However, there is a lack of research on support provision to elite athletes and the views of athletes` support providers. This study addressed this gap by exploring the experiences of providing and receiving support between female Olympians and their main support providers. Five female Olympians and their main support providers participated in separate semistructured interviews. It appeared that support provision was personally and professionally rewarding, as well as challenging, for support providers, and athletes were generally satisfied with the support they received. Athletes appeared highly dependent on their support providers, but both athletes and support providers felt that high levels of support were necessary for athletic success. Further research is needed to understand how support providers are able to foster their own personally supportive relationships and whether high levels of interpersonal dependence are required to achieve athletic success.